Characterizing multi-photon quantum interference with practical light sources and threshold single-photon detectors. (12th April 2018) - Navarrete, Álvaro; Wang, Wenyuan; Xu, Feihu; Curty, Marcos
Abstract: The experimental characterization of multi-photon quantum interference effects in optical networks is essential in many applications of photonic quantum technologies, which include quantum computing and quantum communication as two prominent examples. However, such characterization often requires technologies which are beyond our current experimental capabilities, and today's methods suffer from errors due to the use of imperfect sources and photodetectors. In this paper, we introduce a simple experimental technique to characterize multi-photon quantum interference by means of practical laser sources and threshold single-photon detectors. Our technique is based on well-known methods in quantum cryptography which use decoy settings to tightly estimate the statistics provided by perfect devices. As an illustration of its practicality, we use this technique to obtain a tight estimation of both the generalized Hong−Ou−Mandel dip in a beamsplitter with six input photons and the three-photon coincidence probability at the output of a tritter.